The Effect of Gamification-Based Peer Learning on CPR Knowledge and Self-Efficacy Among Secondary School Students: A Quasi-Experimental Study - Muhammad Purqan Nur; Nasriani Nasriani; Andi Aridhasari Sudirman; Sitti Maryam Bachtiar; Andi Sudirman (Media Kesehatan Politeknik Kesehatan Makassar, 2026)
Noncommunicable diseases are the leading cause of global mortality, and one of their serious complications is sudden cardiac arrest, which requires immediate intervention through cardiopulmonary resuscitation (CPR). CPR education at the school level is crucial for enhancing students’ readiness to respond to cardiac arrest incidents outside of hospitals. This study aims to evaluate the effectiveness of gamification-based CPR training in improving knowledge and self-efficacy among high school students. A quasi-experimental study with a pretest–posttest control group design was conducted on 90 students. The intervention group received CPR training based on American Heart Association (AHA) guidelines through peer-to-peer learning integrated with gamification elements. The control group received peer-to-peer CPR training without gamification. The sample was selected using stratified random sampling based on grade level. Data were analyzed using the Wilcoxon Signed-Rank and Mann–Whitney U tests with a significance level of α = 0.05. The results showed that the intervention group experienced a significant increase in knowledge (p < 0.001) and self-efficacy (p = 0.010), while the control group experienced a significant increase in knowledge (p < 0.001), but not in self-efficacy (p = 1.000). In the between-group analysis, post-test knowledge scores differed significantly with a small effect size (p = 0.039; Cohen’s d = 0.262), but the change in knowledge scores did not differ significantly (p = 0.795; Cohen’s d = 0.030). Significant differences were found in post-test self-efficacy (p = 0.009; Cohen’s d = 0.436) and changes in self-efficacy (p = 0.002; Cohen’s d = 0.555). Gamification-based CPR training is associated with increased knowledge and self-efficacy among high school students. However, this increase in knowledge was not significantly different from that of the control group. Therefore, gamification may be particularly beneficial for enhancing students’ self-efficacy and their readiness to provide first aid in out-of-hospital cardiac arrest situations.